ANALISIS METODE REKRUTMEN DAN SELEKSI MELALUI PENERAPAN TEKNOLOGI INFORMASI DI KANTOR POS GUNUNGSITOLI - Firdaus Telaumbanua; Palindungan Lahagu; Syah Abadi Mendofa; Meiman Hidayat Waruwu (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze the recruitment and selection methods through the application of information technology at the Gunungsitoli Post Office. The objectives of this research are to understand the application of information technology in the recruitment and selection process, identify efforts that can be made to improve the effectiveness of technology implementation, and understand the challenges faced in implementing information technology. This research uses a qualitative method with a descriptive approach, where data was collected through interviews with related parties at the Gunungsitoli Post Office. The results of the study indicate that the application of information technology has helped accelerate the recruitment and selection process, improved accuracy in selecting candidates, and facilitated the management of applicant data. However, there are still challenges such as limited human resources skilled in using technology and technical constraints affecting system smoothness. Therefore, efforts to increase effectiveness can be carried out through employee technology training and improving the technological infrastructure at the Gunungsitoli Post Office. The implementation of information technology in the recruitment and selection process needs continuous improvement to run more effectively and efficiently.